2022
DOI: 10.1159/000525652
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Risk Factors of Incident Small and Large Drusen in the Copenhagen Twin Cohort Eye Study: A 20-Year Follow-Up

Abstract: Introduction: The transition from a normal fundus to one with early drusen (≥ 20 small hard drusen) to age-related macular degeneration (AMD) in the form of drusen ≥ 63 µm in diameter is of interest, because small hard drusen may be precursors of large drusen. Study of AMD precursors lesions may provide valuable insight into factors that initiate AMD. Here, the progression of drusen was studied over an interval of 20 years in a population-based twin cohort. Methods: Single-center, 20-year follow-up of 138 tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…25,26 In 138 twins of 69 pairs, the 20-year incidence of developing $20 small hard drusen and drusen $63 mm was 5.6% and 13.1%, respectively. 5 This study also reported that unshared environmental effects (smoking, diet, lifestyle, and physical activity) explained one-half of incident larger drusen (that will enlarge over time), with aging and smoking equal in impact to genetics. 5 Numerous complement genes are strongly expressed in cells of the choroid, 27,28 and drusen themselves are notably immunoreactive for complement proteins.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…25,26 In 138 twins of 69 pairs, the 20-year incidence of developing $20 small hard drusen and drusen $63 mm was 5.6% and 13.1%, respectively. 5 This study also reported that unshared environmental effects (smoking, diet, lifestyle, and physical activity) explained one-half of incident larger drusen (that will enlarge over time), with aging and smoking equal in impact to genetics. 5 Numerous complement genes are strongly expressed in cells of the choroid, 27,28 and drusen themselves are notably immunoreactive for complement proteins.…”
Section: Discussionmentioning
confidence: 75%
“…5 This study also reported that unshared environmental effects (smoking, diet, lifestyle, and physical activity) explained one-half of incident larger drusen (that will enlarge over time), with aging and smoking equal in impact to genetics. 5 Numerous complement genes are strongly expressed in cells of the choroid, 27,28 and drusen themselves are notably immunoreactive for complement proteins. These genes may regulate outflow in the successive barrier model (above) and respond by resident and transient immune cells of the choroid.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We identified three participants where large drusen had developed in a place previously occupied by small hard drusen. Also, having ≥ 20 small hard drusen at baseline increased the 20-year risk of developing larger drusen [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…They typically have a diameter smaller than 63 μm [ 1 3 ]. Our study group showed in a recently published 20-year follow-up twin study that ≥ 20 small hard drusen is significantly associated with drusen ≥ 63 μm [ 4 ], which is the conventional threshold for diagnosing age-related macular degeneration (AMD). In the Watermen Study, the presence of numerous (≥ 5) small hard drusen was associated with a higher incidence of soft drusen ≥ 63 μm [ 5 ].…”
Section: Introductionmentioning
confidence: 99%